Criminal Liability for the Homicide of an Abusive Husband by a Wife as a Domestic Violence Victim: Normative Ambiguity of Self-Defense and a Victim-Sensitive Interpretation in Indonesian Criminal Law - Putu Dea Anindita Putri Biantara; Diah Ratna Sari Hariyanto (International Journal of Business, Law, and Education, 2026)
This article examines the criminal liability of a wife who kills her husband after prolonged domestic violence, focusing on the normative ambiguity of self-defense and excessive self-defense under Indonesian criminal law. The study is motivated by a recurring doctrinal problem: homicide provisions formally apply to every person who unlawfully takes another person’s life, whereas the factual background of domestic violence often involves cumulative abuse, psychological domination, fear, and survival-based decision-making. The article applies normative legal research using statutory, conceptual, and systematic interpretive approaches. Primary legal materials include Law Number 1 of 2023 on the Criminal Code and Law Number 23 of 2004 on the Elimination of Domestic Violence, while secondary materials include criminal law doctrine, victimology, gender-based violence scholarship, and selected comparative literature on battered women who kill abusive partners. The analysis finds that Article 43 of the 2023 Criminal Code, which recognizes excessive self-defense caused by severe mental disturbance resulting from an unlawful attack or threat of attack, remains insufficiently determinate when applied to domestic violence because it does not define clear criteria for severe mental disturbance or adequately address continuous and cumulative violence. Law Number 23 of 2004 can function as a systematic interpretive instrument because it legally recognizes physical, psychological, sexual, and economic/neglect-based violence within the household. Accordingly, the article proposes a victim-sensitive framework for judicial assessment that integrates the pattern of prior violence, causal connection between abuse and the lethal act, psychological evidence, the survivor’s perception of imminent danger, proportionality, and available safe alternatives. Such an approach is necessary to reconcile legality, culpability, legal certainty, and substantive justice in cases where a domestic violence victim becomes a homicide defendant.